2012
DOI: 10.1021/jf2038532
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Phenolic Antioxidant from the Pacific Oyster (Crassostrea gigas)

Abstract: Using an oxygen radical absorbance capacity (ORAC) assay, antioxidant activity was detected in the ethanol extract of the Pacific oyster, which was purified by sequential extraction with organic solvents. The ethyl acetate fraction showed the strongest antioxidant activity and was further purified, yielding a single compound [as assessed by thin-layer chromatography (TLC) and reverse-phase high-performance liquid chromatography (HPLC)]. This compound was identified as 3,5-dihydroxy-4-methoxybenzyl alcohol on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 29 publications
1
56
0
2
Order By: Relevance
“…There was a pronounced increase in the number of new metabolites reported from molluscs when compared with recent years. The antioxidant activity detected in Japanese samples of the Pacic Oyster (Crassostrea gigas) was attributed to 3,5-dihydroxy-4-methoxybenzyl alcohol, 876 previously reported from the brown alga Leathesia nana. 877 The new C-terminus pyroglutamate gonadotropin-releasing hormone related peptides Cg-GnRH-a 1124 and Cg-GnRH-G 1125 were isolated from French (Normandy) specimens of the Pacic Oyster.…”
Section: Molluscssupporting
confidence: 63%
“…There was a pronounced increase in the number of new metabolites reported from molluscs when compared with recent years. The antioxidant activity detected in Japanese samples of the Pacic Oyster (Crassostrea gigas) was attributed to 3,5-dihydroxy-4-methoxybenzyl alcohol, 876 previously reported from the brown alga Leathesia nana. 877 The new C-terminus pyroglutamate gonadotropin-releasing hormone related peptides Cg-GnRH-a 1124 and Cg-GnRH-G 1125 were isolated from French (Normandy) specimens of the Pacic Oyster.…”
Section: Molluscssupporting
confidence: 63%
“…A recent review of the diterpenes in question suggested a grouping of diterpenes based on biosynthetic origins and also diterpene cyclization complexity [73]. The grouping separates the diterpenes into three groups, Group I (112-134, 136-140), Group II (135, 141-175) and Group III (176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192). Group I diterpenes are all compounds derived from the apparent first cyclization of the pre-cursor geranyl-geraniol between positions C-1 and C-10.…”
Section: Sesquiterpenes and Monoterpenesmentioning
confidence: 99%
“…In a 2012 study a methylated derivative of compound 493 was isolated from the pacific oyster Crassostrea gigas. This compound was shown to be an active antioxidant agent displaying potent activity in DPPH assays [183,184]. A summary of all the miscellaneous classes of compounds isolated from red algae is given in the Supporting Information Figure S32.…”
Section: Miscellaneousmentioning
confidence: 99%
“…The oyster is a rich source of dietary protein and other nutrients, such as carbohydrates, lipids, polyunsaturated fatty acids and minerals (Pennarun et al 2003 ; Cheng et al 2013 ). It has been described that the extract of C. gigas exhibits antioxidant activity (Watanabe et al 2012 ). Recently, a phenolic antioxidant from the oyster has been identified (Watanabe et al 2012 ; Yoshikawa et al 1997 ).…”
Section: Introductionmentioning
confidence: 99%